Spectrally resolved localized states in GaAs1−xBix. (1st February 2017) - Christian, Theresa M.; Alberi, Kirstin; Beaton, Daniel A.; Fluegel, Brian; Mascarenhas, Angelo
Abstract: The role of localized states and their influence on the broader band structure remains a crucial question in understanding the band structure evolution in GaAs1− x Bi x . In this work, we present clear spectroscopic observations of recombination at several localized states in GaAs1− x Bi x . Sharp and recognizable photoluminescence features appear in multiple samples and redshift as a function of GaBi fraction between x = 0.16% and 0.4% at a linearized rate of 34 meV per % Bi, weaker than the redshift associated with band-to-band recombination. Interpreting these results in terms of radiative recombination between localized holes and free electrons sheds light on the relative movement of the conduction band minimum and the characteristics of localized bismuth-related trap states in GaAs1− x Bi x alloys.